Predefined Object Reduction - Mohammed, Mohammed Adam Taheir; Wan Maseri, Wan Mohd; Ruzaini, Abdullah Arshah; Liu, Yao (IJARCET, 2013)
Reduction techniques is still an open area to be explored in knowledge management. This paper defines algorithm known as Predefined Hybrid Reduction which generate its conditions for object co occurrences of original data then execute Hybrid Reduction data for their data to perform extractions. Predefined Hybrid Reduction give a proper solution for expansion the data set , it select significant object with high quality of informations, it delete every object not satisfies their conditions. It show appropriate relevant result. It provide better reduction without inconsistency problem unlike data comparisons. It manage the inferior object which store only significant data based on predefined confidence and predefined support for maintain the inferior object then Hybrid reduction which are dual reduction. As part of this proposal, a comparison test with Hybrid reduction. The conclusion part which shows better alternative result through our model